Strategi Mengembangkan UMKM Dengan Optimalisasi E-Commers - Chavid Moyo Jaladri,; Rosi Ani Prayekti, (JOURNAL KOPERASI DAN MANAJEMEN, 2023)
Purpose – In tackling poverty and unemployment, an entrepreneurial spirit is needed. The growth of entrepreneurs will encourage national economic growth. The strategies used to develop businesses and increase turnover in the current digital era are very different from previous eras. Design/methodology/approach – The research method used in this journal is a qualitative method because this journal describes strategies for developing a business in the digital era. Findings – Business development is an effort that must be carried out by various parties involved in the business, including the government, local government, communities, and entrepreneurs themselves, to develop their business into a larger business with high competitiveness through the provision of side-by-side facilities and guidance accompanied by motivation and productivity. Research limitations/implications – This study uses more subjective informants, who have a strong risk of reducing the objectivity of the research results. The character of the researcher will affect the results of the research; it could be that when you meet other researchers with different characters, the results will be different. Originality/value – Business success or continuity is needed to grow and develop in the market (Kurniawati, Santoso, & Widowati, 2019). In this study, the market is very influential on the business strategic plans carried out by MSMEs.